A promising area of research in medicine: recent advances in properties and applications of Lactobacillus-derived exosomes - Liu, Rui (Frontiers in Microbiology, 2024)
Lactobacillus-derived exosomes, small extracellular vesicles released by bacteria, have emerged as a promising area of research in recent years.These exosomes possess a unique structural and functional diversity that allows them to regulate the immune response and promote gut health. The isolation and purification of these exosomes are crucial for their effective use as a therapeutic agent. Several isolation and purification methods have been developed, including differential ultracentrifugation, density gradient centrifugation, and size-exclusion chromatography. Lactobacillus-derived exosomes have been demonstrated to have therapeutic potential in various diseases, such as inflammatory bowel disease, liver disease, and neurological disorders. Moreover, they have been shown to serve as effective carriers for drug delivery. Genetic engineering of these exosomes has also shown promise in enhancing their therapeutic potential. Overall, Lactobacillus-derived exosomes represent a promising area of research for the development of novel therapeutics for immunomodulation, gut health, and drug delivery.